MEMS FABRICATION USING PµSL TECHNIQUE BASED 3D PRINTER - (:unkn) unknown (My University, 2020)
This study aims to fabricate Electro-Thermal Micro Actuator based on Micro Electro Mechanical System (MEMS) with a 3D printer using Projection Micro Stereo Lithography (PµSL) technique. The production of the actuator produced by traditional MEMS fabrication methods with a 3D printer has been carried out in this study. The cost of traditional MEMS fabrication methods is high and there are many techniques to achieve the process. On the other hand, some methods have been developed to obtain better quality and low-cost production as a parallel to the development of technology. One of these methods is to use 3D printers employing the PµSL technique. By means of these printers, it is possible to reduce both the cost and workload of the production process the MEMS systems. In this study, it is investigated and stated that Nano level fabrication would be possible with 3D printers in the following years. It can also be predicted that traditional MEMS production methods will be replaced by 3D printers soon.